Left ventricular remodelling pattern and its relation to clinical outcomes in patients with severe aortic stenosis treated with transcatheter aortic valve implantation - Rymuza, Bartosz; Zbroński, Karol; Scisło, Piotr; Wilimski, Radosław; Kochman, Janusz; Ćwiek, Agata; Filipiak, Krzysztof J.; Opolski, Grzegorz; Huczek, Zenon (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction : Left ventricular hypertrophy (LVH) is a common compensating process in the pressure overload mechanism of aortic stenosis (AS). Aim : To identify a group of patients with a LVH pattern which may alter periprocedural and 1-year outcomes after transcatheter aortic valve implantation (TAVI). Material and methods : Echocardiographic examinations of 226 patients with severe AS treated with TAVI between March 2010 and February 2016 were retrospectively analysed and correlated with echocardiographic parameters and clinical outcomes in the study group. Ultimately 208 patients were enrolled in the study. Based on left ventricular mass index (LVMI) and relative wall thickness (RWT) patients were divided into three categories: concentric remodelling (CR), concentric hypertrophy (CH) and eccentric hypertrophy (EH). Most of the patients with severe AS referred for TAVI were found to have CH (n = 150, 72.8%), then EH (n = 33, 16%) and CR (n = 16, 7.8%). Results : There were no significant differences between groups in terms of periprocedural outcomes or complications. After a mean observation time of 561.8 ±239.0 days, the observed all-cause mortality rate was 19.9%. After multivariable adjustment, CR remained associated with a higher risk of mortality (HR = 4.31; 95% CI: 1.607–11.538; p = 0.004). Conclusions : Left ventricular hypertrophy is common in patients with severe AS prior to TAVI. The LVH pattern does not affect TAVI-related complications. In patients with severe AS referred for TAVI, CR seems to be the least favourable geometry of LVH, increasing the risk of 1-year all-cause death.